Genre Hybridization in the “Musradiyya” “The Lyricism of Love and Blood” by Azzedine Djelaoudji - achour, fatimazohra (El Omda in Linguistics and Discourse Analysis, 2026)
This research is to recognize one of the forms of experimentation in the play, by recognizing the term: "masradia" and the writing experience according to its giving to Algerian innovator Azzedine djelaoudji. Which aspires to give the stage a dynamic match The vitality of narrative in contemporary literature. And that the show will not remain on stage and has a wider audience . In this sense, the masradia of love and blood was an experimental model Races overlap and create a world. The old Arab narrative and contemporary narrative are combined in harmony that serves new issues.